Manual de procedimientos para la empresa de agua potable y alcantarillado EMAPA regional La Estancilla, en el área de recursos humanos. - Beltran Conforme, Estela Auxiliadora (2010)
This investigation is intended to create a Manual of Procedure for the Company of Water and Sewerage EMAPA, for which set a goal general implement a manual for the Human Resources administration of the Company. To fulfill this goal was carried out a methodological design in which specifies the type of research that has been applied the what was the descriptive or field, for this reason was prepared questions of interview addressed to the Director of Human Resources, and produced a survey which was applied to the company employees in different cities where it is the offices of the Company Emapa Regional The Estancilla On the basis of results of the interview and the survey for the development of the Manual that the Company needs, combined with other investigations of procedural manuals already developed, to obtain a manual more concise and which can provide the necessary information for the Company. The operational responsibility of the staff specifies the charge, the area to which it belongs, to whom should lead, and the functions of each company staff. The Department of Human Resources, is as integral vision, maintain control of the functions of each employee of the company, and the doubts that the employee came to take. Be prepared a manual of procedure using a design easy to understand and have the necessary information to provide the knowledge that employees.